Top Management Team Intrapersonal Functional Diversity and Adaptive Firm Performance: The Moderating Roles of the CEO–TMT Power Gap and Severity of Threat - Ma, Changlong; Ge, Yuhui; Wang, Jingwei (Frontiers in Psychology, 2021)
While usually argued to be improving firm performance, the effect of top management team (TMT) functional diversity on firm performance is mixed. Bridging the TMT diversity, team adaptation, and threat-rigidity literature, we present a contingency model in which the relationships between intrapersonal functional diversity (at both CEO and TMT levels) and adaptive firm performance depend on the CEO–TMT power gap and severity of threat. To test our hypotheses, 270 firms, which have been severely affected due to the COVID-19 pandemic, were selected from China's A-share listed companies. Multiple regression analyses have shown that a moderation of CEO intrapersonal functional diversity's effect on adaptive firm performance by the CEO–TMT power gap is moderated by the severity of threat. However, no significant main or interaction effect of TMT intrapersonal functional diversity was found. The findings of this study have implications for the recovery or improvement of firm performance in threat situations.